Tingkat Kepuasan Pasien Terhadap Pelayanan Homecare Di Wilayah Kerja Puskesmas Baula - Sitti Herliyanti Rambu (Lembaga Pengembangan Kinerja Dosen, 2024)
Home care is a comprehensive service for individuals and families at home which aims to minimize the impact of disease and increase the independence of patients and families in the care and treatment of family members who experience health problems. Patient satisfaction with health services is something that needs to get attention from providers. health services in carrying out their role, while obstacles are still found in homecare services. The aim is to determine the level of patient satisfaction with homecare services. Research method This type of research uses a descriptive research design with a survey method. This research was conducted in the Baula Community Health Center working area with a sample size of 30 respondents. The results of this research show that the level of patient satisfaction with homecare services in the Baula Community Health Center working area was that most respondents were satisfied, namely 83.3%. Conclusion Patient satisfaction is an important indicator of quality nursing services.